(untitled) (Dhaka University Journal of Science, 2017)
This paper concentrates on choosing the appropriate smoothing constants for Exponential Smoothing method and Holt’s method. These two methods are very important quantitative techniques in forecasting. The accuracy of forecasting of these techniques depends on Exponential smoothing constants. So, choosing an appropriate value of Exponential smoothing constants is very crucial to minimize the error in forecasting. In this paper, we have showed how to choose optimal smoothing constants of these techniques for a particular problem. We have demonstrated the techniques by presenting a real life example and calculating corresponding forecast value of these two techniques for the optimal smoothing constants. Dhaka Univ. J. Sci. 65(1): 55-59, 2017 (January)